ATG5 as biomarker for early detection of malignant mesothelioma - Tomasetti, Marco; Monaco, Federica; Strogovets, Olga; Volpini, Luca; Valentino, Matteo; Amati, Monica; Neuzil, Jiri; Santarelli, Lory (BMC research notes, 2023)
OBJECTIVES: Malignant pleural mesothelioma (MPM) is an aggressive disease with grim prognosis due to lack of effective treatment options. Disease prediction in association with early diagnosis may both contribute to improved MPM survival. Inflammation and autophagy are two processes associated with asbestos-induced transformation. We evaluated the level of two autophagic factors ATG5 and HMGB1, microRNAs (miRNAs) such as miR-126 and miR-222, and the specific biomarker of MPM, soluble mesothelin related proteins (Mesothelin) in asbestos-exposed individuals, MPM patients, and healthy subjects. The performance of these markers in detecting MPM was investigated in pre-diagnostic samples of asbestos-subjects who developed MPM during the follow-up and compared for the three groups. RESULTS: The ATG5 best distinguished the asbestos-exposed subjects with and without MPM, while miR-126 and Mesothelin were found as a significant prognostic biomarker for MPM. ATG5 has been identified as an asbestos-related biomarker that can help to detect MPM with high sensitivity and specificity in pre-diagnostic samples for up to two years before diagnosis. To utilize this approach practically, higher number of cases has to be tested in order to give the combination of the two markers sufficient statistical power. Performance of the biomarkers should be confirmed by testing their combination in an independent cohort with pre-diagnostic samples.
Keywords: Mesothelioma, Malignant; nádory plic; Autophagy-Related Protein 5; Lung Neoplasms; Humans; ATG5; nádory pleury; časná diagnóza; MicroRNAs; Biomarkers, Tumor; Pleural Neoplasms; Mesothelin; HMGB1; lidé; Asbestos; Biomarkers; GPI-Linked Proteins; Atg5; miRNAs; Asbestos exposure; Malignant pleural mesothelioma; nádorové biomarkery; Mesothelioma; mezoteliom; Early Diagnosis; mezotelin; maligní mezoteliom; mikro RNA; azbest; GPI-vázané proteiny